Kesiapan Remaja Menghadapi Menarche Melalui Pendidikan Kesehatan Metode Peer Group - Putri, Prahardian; AIP, Yolanda; Yulia, Sri (JKM : Jurnal Keperawatan Merdeka, 2024)
Background: Menarche is a condition when a woman experiences her first menstruation. Menarche is a crisis situation for the growth and development of adolescent girls because it can cause embarrassment, anxiety and fear. One way for young women to have readiness to face menarche is to provide information about menstruation correctly through health education. The purpose of this study was to determine the effect of peer group health education method on adolescents' readiness to face menarche. Methods: This study was conducted using quasy experimental method with nonequivalent control group design. The sample size was 92 respondents with probability sampling technique. The analysis used Two Independent Sample Test with Mann Whitney. Results: This study shows the effect of peer group method health education on adolescents' readiness to face menarche. Conclusion: Adolescent readiness in facing menarche is increased to the provision of peer group method health education.